2003
DOI: 10.2188/jea.13.162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet and Helicobacter pylori Infection to the Risk of Early Gastric Cancer.

Abstract: BACKGROUND: The association of dietary habits and Helicobacter pylori infection with early gastric cancer is still unclear.METHODS: A hospital-based case-control study was conducted in Korea. Sixty-nine patients were newly diagnosed as having early gastric cancer at the Division of Gastroenterology, Asan Medical Center, and 199 healthy subjects who visited the Health Promotion Center of the this same hospital for annual health examinations were selected as controls. Helicobacter pylori infection status was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 14 publications
3
103
3
1
Order By: Relevance
“…[26][27][28][29][30][31][32] A large number of studies that have examined this relationship have generally found an increased risk by approximately 2-fold for frequent consumption of salt and salted foods. The relationship is also biologically plausible, given that salt may lead to damage of the protective mucosal layer of the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] A large number of studies that have examined this relationship have generally found an increased risk by approximately 2-fold for frequent consumption of salt and salted foods. The relationship is also biologically plausible, given that salt may lead to damage of the protective mucosal layer of the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Almost certainly, these include a more varied diet and better food conservation, including refrigeration, as well as control of infection by Helicobacter pylori (H pylori) (22,23) , decreasing of risk factors exposure, such as consumption of salt and salty foods, which can lead to damage of the protective layer of the mucosa of stomach (11,22) and smoking (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Some of the previously reported positive findings regarding the association between salt and gastric cancer might reflect confounding by infection with H. pylori (21), a strong and well-established risk factor for stomach cancer (18), and this infection could act as an effect modifier regarding the effect of sodium on the gastric mucosa (22,23). High salt intake might also be associated with an increased risk of H. pylori infection (19,20).…”
Section: Discussionmentioning
confidence: 99%